Monitoring health problems and training to support performance in competitive cross-country ski athletes - Karlsson, Ø. (Mid Sweden University, 2022)
Competitive cross-country (XC) ski athletes (defined hereafter as XC skiers and biathletes combined) are vulnerable to developing various health-related symptoms and conditions due to several factors, such as high physiological and psychological demands, extreme competition and training environments, high training loads, demanding competition schedules, and frequent travel. On initiating this work, we (the author and supervisory team) were approached by the Swedish Ski Association (SSF) and the Swedish Biathlon Federation (SSSF) to investigate the relationships between training, racing, and health problems, with a specific focus on illnesses (rather than injuries), and an ultimate goal of improving future support practices and athletic performance. The project coincided with the teams` Olympic-cycle preparations for the 2022 Beijing Olympic Winter Games, which were held at an altitude of ~ 1700 m. Therefore, optimizing preparation to competitions at altitude was also a key concern for the two sports organizations.